2020
DOI: 10.1093/mnrasl/slaa004
|View full text |Cite
|
Sign up to set email alerts
|

Not so fast: LB-1 is unlikely to contain a 70 M⊙ black hole

Abstract: The recently discovered binary LB-1 has been reported to contain a ∼ 70 M black hole (BH). The evidence for the unprecedentedly high mass of the unseen companion comes from reported radial velocity (RV) variability of the Hα emission line, which has been proposed to originate from an accretion disk around a BH. We show that there is in fact no evidence for RV variability of the Hα emission line, and that its apparent shifts instead originate from shifts in the luminous star's Hα absorption line. If not account… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 29 publications
0
48
0
1
Order By: Relevance
“…As Liu et al (2019) notes, the Hα line appears to exhibit a low-amplitude, anti-phase motion relative to the primary star, leading the authors to speculate that it originates in an accretion disk around a ≈70 M BH secondary. However, Abdul-Masih et al (2020) and El-Badry & Quataert (2020) have since independently shown that this anti-phase signature can be explained as a spurious result that emerges from the motion of the broad absorption wings of the B-type primary on top of a static Hα line. These results cast doubt on the measurement of the large mass of the secondary from Liu et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…As Liu et al (2019) notes, the Hα line appears to exhibit a low-amplitude, anti-phase motion relative to the primary star, leading the authors to speculate that it originates in an accretion disk around a ≈70 M BH secondary. However, Abdul-Masih et al (2020) and El-Badry & Quataert (2020) have since independently shown that this anti-phase signature can be explained as a spurious result that emerges from the motion of the broad absorption wings of the B-type primary on top of a static Hα line. These results cast doubt on the measurement of the large mass of the secondary from Liu et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Both these aspects were, however, challenged by subsequent studies. El-Badry & Quataert (2020a) and Abdul-Masih et al (2020) showed that the anti-phase signature of Hα cannot be readily interpreted as Doppler motion without considering the impact of potential Hα absorption of the B-type component. Simón-Díaz et al (2020) and Irrgang et al (2020) performed spectroscopic studies of the primary and found evidence for processed CNO material in its atmosphere, leading Irrgang et al (2020) to suggest that it is a low-mass stripped helium star.…”
Section: Introductionmentioning
confidence: 99%
“…The scatter in velocities at large distances from the Sun is due to the black holes that have wandered into the halo and no longer follow the bulk motion of the disk. from their stellar companions; these black holes tend to have masses ≲20M ⊙ [16,17,74] (with the possible exception of LB-1, which has been claimed to have a mass of 70M ⊙ [75], although this is controversial [76,77]). In contrast, the mass distribution of black holes in merging binaries detected by LIGO and Virgo is consistent with a mass cutoff of approximately M BH ∼ 40M ⊙ and a powerlaw index of around 2 [78][79][80]; however, it is difficult to extrapolate from the properties of the gravitationally detected black holes, as these are found in other Galaxies with unknown star formation histories and metallicities.…”
Section: B Choice Of Mass Distributionmentioning
confidence: 99%